Special Education Teachers’ Perceptions of the Factors lead to School Bullying of Students with Intellectual Disabilities in Asir (Journal Of Educational and Psychological Researches, 2023)
AbstractThis study aims to identify the most prominent factors that lead to bullying of students with intellectual disabilities in primary and middle schools from the perspectives of special education teachers. A quantitative descriptive approach was utilized. A questionnaire was used as a tool for data collection. The sample consisted of (72) male and female teachers from the Asir region in the Kingdom of Saudi Arabia. The results revealed the most prominent factors that lead to bullying as follows: factors associated with the school and its policies, factors associated with peers, factors associated with students with intellectual disabilities, and factors associated with general education teachers. The findings also showed that there are no statistically significant differences in the responses of male and female teachers due to gender, educational qualification, and years of teaching experience. In light of the results of the research, the most prominent recommendations and suggestions related to protecting students with intellectual disabilities from bullying and raising awareness of such behaviors in schools were provided and discussed.